Penentuan Klaster Wilayah Kecamatan Berdasarkan Pusat Pelayanan Masyarakat di Wilayah Kepulauan Kabupaten Maluku Tengah Provinsi Maluku - Ilham Marasabessy; Abdullah Marasabessy; Oki Nurul Asma Tualeka; Desmi Insu Tualeka (Institut Pertanian Bogor, 2021)
The connectivity of a region is an indicator the growth of service centers. Community service is carried out with a team from PT. Maluku and North Maluku Regional Development Bank Central Maluku Branch during 2018. Data were collected in 18 districts in Central Maluku Regency through the Rapid Survey Method for regional potential and socio-economic dynamics of the community. Central Maluku Regency BPS data support 2018 is a complementary input in the centrality analysis. The data were processed using quantitative descriptive analysis using Guttman scale/Marshall Centrality Index and spatial analysis tools using ArcmapGIS 10.3.1 software, to obtain a map of the regional service center. Central Maluku Regency is an archipelago, having district clusters spread over Seram Island, Ambon, Lease Islands and Banda. The district cluster is divided into 4 regions with the highest level of regional service being in Amahei District (11.14) and the lowest in Nusa Laut (2.50). Economic growth in sub-districts in the archipelago experienced a positive trend, concentrated on Ambon Island and Banda Islands, while the Lease Islands centrality index was in the lower middle category.